Doctors', Patients' and Physician Associates' Perceptions of the Physician Associate Role in the Emergency Department - Nicole M. A. King; Suzannah Helps; Yee Gan Ong; Sandra Walker (Wiley, 2024)
Abstract Introduction The Emergency Department (ED) has seen increased patient attendance and difficulty meeting demands. New healthcare professions such as Physician Associates (PAs) are being utilised to complement the existing medical workforce. Despite the growth of their professions in the United Kingdom, little evidence is available about the perceptions of their roles. Objective This study aims to provide evidence of doctors', PAs' and patients' perceptions of the PA role in the UK ED. Methods A mixed methods approach consisted of the following: 1. An online exploratory survey of ED doctors at one English ED over 1 month (February-March 2022). 2. Post consultation semi‐structured patient questionnaires over 2 weeks (April 2022). 3. Semi‐structured virtual interviews with ED consultants across the four regions of the United Kingdom (3 months in 2022). 4. Semi‐structured virtual interviews with ED PAs across the four regions of the United Kingdom (3 months in 2022). The analysis methods that were used included frequency counts and percentages from closed questions, and hybrid thematic analysis of free text and interview transcripts. Results Four ED consultants and four ED PAs across the United Kingdom were interviewed. Twenty‐eight ED doctors participated in the online survey. Fifty‐seven patients completed the post consultation questionnaire. Four main themes (PAs being fit for purpose; patient recognition of PAs, PAs providing continuity of care, and future PAs and regulation) were deduced as per the General Medical Council, Good Medical Practice domains (knowledge, skills and development; patients, partnership and communication; colleagues, culture and safety; and trust and professionalism). Other subthemes were induced via hybrid thematic analysis. In this study, doctors and patients had mixed comments about the role of PAs. Most of them were positive as doctor participants perceived PAs to be knowledgeable, highly skilled, with mostly good communication skills, team players, providing continuity of care and overall being fit for purpose. However, some doctor participants commented negatively about PAs for providing little quality healthcare and being inexperienced. There was a desire for career progression among the PA participants and a need to work to their full potential. Although the clinicians of this study displayed a clear understanding of the PA role in the ED, a high frequency of surveyed patients mistook PAs for doctors. It was suggested that future PAs could complete a postqualification programme in emergency medicine, combine roles, be paid on an alternative scale and be formally regulated. Conclusion In this study, mixed views were expressed by ED consultants, ED junior doctors and patients regarding the role of the PA in the ED. Stakeholders can use the information presented to develop a better understanding of the perceptions of the PA role within the UK ED. Patient or Public Contribution The Patient and Public Involvement and Engagement (PPIE) group, led by Healthwatch, made significant contributions to the study's design by providing valuable feedback on the information sheets and consent forms utilised. The patients' responses helped guide the study's direction and shape its future work. As part of the dissemination activities, the study findings was shared with both the PPIE team and Healthwatch media production team.